2020
DOI: 10.1021/acs.estlett.0c00605
|View full text |Cite
|
Sign up to set email alerts
|

Four-Month Changes in Air Quality during and after the COVID-19 Lockdown in Six Megacities in China

Abstract: The pandemic of coronavirus disease 2019 (COVID-19) resulted in a stringent lockdown in China to reduce the infection rate. We adopted a machine learning technique to analyze the air quality impacts of the COVID-19 lockdown from January to April 2020 for six megacities with different lockdown durations. Compared with the scenario without lockdowns, we estimated that the lockdown reduced ambient NO 2 concentrations by 36–53% during the most restrictive periods, which involved Level-1 publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 23 publications
5
114
0
Order By: Relevance
“…Goldberg [8] showed the existence of drops in NO 2 levels in several US cities using transport and satellite data. Krecl et al in their recent study [9] have reported similar findings for the city of Sao Paulo, and identical patterns were found by Wang [10] in six sites in China. Some studies focused on the spatiotemporal dynamics of the disease including environmental effects, socioeconomic factors, health service resources, and demographic conditions that vary from different counties in the United States [11].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Goldberg [8] showed the existence of drops in NO 2 levels in several US cities using transport and satellite data. Krecl et al in their recent study [9] have reported similar findings for the city of Sao Paulo, and identical patterns were found by Wang [10] in six sites in China. Some studies focused on the spatiotemporal dynamics of the disease including environmental effects, socioeconomic factors, health service resources, and demographic conditions that vary from different counties in the United States [11].…”
Section: Introductionsupporting
confidence: 67%
“…The lockdown decrees in many countries provided a unique opportunity to compare the levels of ozone, and particulate matter in urban areas under a reduced influence of human activities. Some of such studies have based their comparisons on point locations [5,9,41] whilst others have used aerial data to make comparisons in pollutant concentrations [8,10]. Ozone spatial and temporal distribution is closely related to NO 2 concentrations, although its dynamics are more difficult to model.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in CO 2 emissions have also been reported globally due to heavily curtailed economic activities (Le Quéré et al, 2020;Forster et al, 2020). Many of the reports of improved air quality were preliminary, and further research was required to fully understand and quantify the improvements observed throughout Europe, particularly after accounting for meteorological factors (Grange et al, 2020;Carslaw, 2020;Lee et al, 2020;Wang et al, 2020;Shi et al, 2021;Fenech et al, 2021;Velders et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At the end of 2019, an epidemic of respiratory disease caused by a novel coronavirus (named as “COVID-19”) started to spread ( Huang et al, 2020 ; Tian et al, 2020 ; Wang et al, 2020 ). As is well known, the disease has become a global pandemic with more than 30 million confirmed cases by September 20, 2020, with over 90000 cases reported in China ( https://coronavirus.jhu.edu/map.html ).…”
Section: Introductionmentioning
confidence: 99%